Piercing Leviathan : God's defeat of evil in the book of Job - Ortlund, Eric Nels (Downers Grove IVP, 2021)
"One of the most challenging passages in the book of Job is the Lord's long description of a hippopotamus and crocodile. In this NSBT, Eric Ortlund argues that Behemoth and Leviathan are better understood as symbols of cosmic chaos and evil, helping readers appreciate the reward of Job's faith (and ours) as we endure in trusting God while living in an unredeemed creation"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Theodicy -- Biblical teaching; Good and evil -- Biblical teaching; Behemoth; Leviathan